Theory of Change, Monitoring, and Evaluation A toolkit for developing a culture of evaluation and learning - Ecorys (West Yorkshire Combined Authority, 2025)

Adaptive Management in International Development - Knowledge Base - Prieto Martin, Pedro (2025)
A curated collection of resources on Adaptive Management and MEL in International Development

Digital.gov Resources - U.Ss GSA (Digital.gov, 2025)
Essential how-to guidance for government product managers and digital teams.

MSD Competency Framework - BEAM Exchange (BEAM Exchange, 2023)
MSD Competency Framework A catalogue of the full range of knowledge, skills and aptitudes found in high-performing teams that use the market systems approach. Useful for: Practitioners - identify personal training needs and continue your professional development Trainers - diversify your courses and refine your training / capacity-building offers Managers - strengthen your recruitment and induction processes MSD competencies Competency is a mix of knowledge, skills and attitudes demonstrated through concrete behaviours. This section explores the 17 competencies used by high-performing MSD teams. Arranged in three groups they relate to how we understand the world, make decisions and interact with others. Each competency is defined and has links to useful resources that explain or illustrate the knowledge or skills that feed it. Where available, sources of teaching and learning for that competency are included. Teaching and learning modes An exploration of the most common modes of teaching and learning that support practitioners to acquire knowledge, skills and attitudes. Some modes of learning are more relevant to certain types of competency - as indicated by the box colours. Each page has a summary of the teaching mode, guidance for team leaders and trainers, and examples of how to use this mode for developing specific competencies. Assessment modes Assessing competency is important for recruitment, performance appraisal and continued professional development These pages describe distinct approaches to evaluating individuals. They include a summary of the evaluation mode, guidance for assessors, and examples tailored to specific competencies.

Re-institute website - RE!NSTITUTE (Re!nstitute, 2023)
We are a dynamic non-profit organization with a unique approach to managing change and catalyzing innovation to support global systems transformation. We know that to achieve equal, just, and safe communities, we must collectively challenge and change the systems that people rely on — especially those most vulnerable. Together, we must RE!BUILD a system's resilience and capacity to take on our biggest generational challenges. Justice, housing, health, and other systems in every country are often struggling to come together, across institutions and organizations, to unite under a common vision for change, and implement those changes in effective and innovative ways. Our work and methodology — the 100-Day Challenge — are designed to support these systems to achieve extraordinary results. Our approach is rooted in the philosophy that frontline staff, supported by leadership, can unleash innovation and achieve incredible results by creating new relationships, experimenting with fresh ideas from across their system, and building authentic engagement with those with lived experience.

Propel - Strhive (2023)
Learn from experience. Together. In the complex landscape of international development, organisations need a way to learn from their experiences and build on what works. Propel is the software solution that revolutionises the way organisations capture, access, and reuse learnings to adapt, innovate, and create lasting change on a global scale. Let's stop reinventing the wheel and build on what works, together.

TIP Resource Lab - Tools, Actions, Learning - TIPC (TIP Resource Lab, 2022)

OutNav - Evaluate outcomes and impact - Matter of Focus (Matter of Focus, 2021)
Make better use of your data and information to learn, improve and tell an evidenced story of the difference your organisation is making.

Online Learning and collaborative platform for systems thinking and systems change - SI (Systems Innovation, 2021)

Thinking Tools Studio - Waters Center (Waters Center for Systems Thinking, 2021)
Tools to help you Think

🔮 Seven lessons from building with AI - Azhar, Azeem (2020)
Plus a stack of 40+ AI tools we use at Exponential View

🔮 Six mental models for working with AI - Azhar, Azeem (2020)
The operating manual we wish we'd had

A Guide To Agile Project Management Methodology & Tools - Aston, Ben (The Digital Project Manager, 2020)
Looking to brush-up on agile? Here's your complete guide to agile project management, agile principles and key components, and the best agile tools for 2020.

Changeroo - Theory of Change platform - Changeroo (2020)
Changeroo assists organisations, programs and projects with a social mission to develop and manage high-quality Theories of Change. It allows you to - together with stakeholders co-create Theories of Change, and - present these in an interactive and engaging way. It helps keep a Theory of Change alive, enables reflective monitoring, and supports capacity building among social organisations. Changeroo helps you utilize your Theory of Change for strategic learning, communication, stakeholder engagement, impact measurement, scaling, planning, monitoring and evaluation. Thus you build a culture of critical thinking, constant analysis, co-creation and continuous learning. In sum, a truly strategic approach to societal value creation that helps you to assist your target groups to flourish!

Theory of Change: From novice to master changemaker - Changeroo (2020)
Theory of Change is more than just a tool or instrument. It is a mindset! A mindset to optimise impact management. As the cornerstone of impact management it is indispensable to any purpose-driven organisation targeting social or environmental value creation. It offers you the cornerstone of a learning approach toward change and impact. A way to build a mindset and organisational culture of critical reflection, co-creation with stakeholders and constant analysis of what works, why, for whom and under what circumstances. Are you ready to take impact management to the next level with the help of Theory of Change? We offer you the premier online course to learn everything about this approach.

ParEvo - Web-assisted participatory evolution of scenarios - Davies, Rick (2020)
ParEvo is a method of exploring alternative futures or histories, using a participatory evolutionary process (hence ParEvo). The process is designed to be used by multiple people, to produce a branching structure of storylines about what did, or could, happen. Participants are anonymous and can choose the extent to which they collaborate with others. Participants are also able to tag, comment on, and evaluate the storylines that are generated. Completed exercises can be analysed using downloaded data describing the content of storylines and the structure of people’s participation. Outcomes can be both cognitive (e.g. how we think about the future) and behavioural (e.g. how we respond to the future).

111 Evaluation Cartoons for Presentations and Blog Posts - Lysy, Chris (2020)

Pando - Root Change (Root Change, 2020)
Pando is a platform that gives organizations a way to visualize, learn from, and engage with the social systems in which they work. We have designed Pando to help users build trust, strengthen relationships, and work together to achieve greater social impact. Grounded in social network analysis, Pando allows users to collect and visualize organizations and their relationships in real-time on simple and easy-to-use relationship maps. Relationship maps are managed by map administrators. These are actors interested in learning about a particular system and making the tool available to those working in the system. Pando is integrated with Keystone Accountability’s Feedback Commons, an online tool that allows map administrators to collect and analyze qualitative feedback about levels of trust and relationship quality among map participants. Key features of Pando include relationship mapping, feedback surveys, and dashboards.

System Innovation Network - Si Network (Si Network, 2020)
The Si Network is an online platform for building the developing of systems innovation - connecting people around the world to learn and apply the ideas and methods of systems innovation towards addressing complex challenges and building better systems that work for all. Not sure what systems innovation is? Systems innovation is a new approach to innovation that tries to tackle complex social and environmental challenges through the use of more holistic & innovation driven approaches. It is a kind of innovation that aims to change the underlying structure of a system, thus potentially enabling a more transformational kind of change - systems change - rather than incremental "innovation as usual". What Do You Do? We are building an ecosystem of individuals and organizations co-learning and co-creating systems innovation across geographies and sectors. This ecosystem is enabled by our online platform which provides educational content, toolkits, organizes events and projects as well as provides various support services for organizations. Purpose Statement Our purpose is to build the world’s capacity for systems innovation - so as to better understand and address complex challenges and co-create a world where systems work for all. We envision a world where everyone thinks in systems and has an understanding of complex systems. From this understanding, we are able to design and develop regenerative systems that work for everyone. Our mission is to grow the field of systems innovation as a pathway to co-learn the ideas of systems thinking and apply them to co-creating new systems Who's Involved? We are a networked organization of some 17K+ members forming part of 20+ hubs in major cities around the world. Our community is broad and diverse in areas of work and interest from designers, innovators, and entrepreneurs, to researchers and management but they all share a common interest in learning and applying systems thinking ideas. The Si platform is developed and managed by a small core team based in London UK. We are registered as a business but operate as a social enterprise focused on our purpose of advancing the area of systems innovation in theory and practice. Core Value Creativity - We put creativity at the centre of what we do. Holding a space for curiosity, diversity of views, exploration and critical thinking as a pathway to transformative innovation. Openness - We strongly believe in openness in our ways of being, thinking and organizing as a sustainable pathway to creating an adaptive, scalable and dynamic community. Growth Mindset - We embrace challenges as opportunities for continuous personal and collective learning and development, with a never-ending potential to grow and start with a new beginning. Perseverance - When facing uncertainty and failure, perseverance is what is needed to maintain commitment and a resilient pathway aligned with our purpose. Care - Care is one of our core principles. We foster relationships based on honesty and empathy, striving to be present and conscious in what we do and taking responsibility for the effects of our actions.